2022
DOI: 10.3389/fphar.2022.929169
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Properties of Hydroxyl Safflower Yellow a in Diabetic Nephropathy: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Diabetic kidney disease (DKD) is a chronic progressive disorder which is a leading cause of chronic kidney disease (CKD). As an important pathogenesis of DKD, the overproduction of reactive oxygen species (ROS) and the inflammatory response have been considered central mediators in the progression of DKD. Herbal products are increasingly being applied as antioxidants and anti-inflammatory agents. Of those, the effect of hydroxyl safflower yellow A (HSYA) on oxidative stress and inflammatory reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Among the pharmacodynamic components of shenkang injection, HSYA comes from safflower, which can inhibit platelet aggregation and release induced by platelet-activating factors, and can competitively inhibit the binding of platelet-activating factors and platelet receptors. HSYA is an effective component of safflower yellow pigment in promoting blood circulation and removing blood stasis [ 22 ]. Tanshinol, derived from Salvia miltiorrhiza, can improve the damage degree of blood vessels and enhance their growth ability, and can effectively play an anti-inflammatory role [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the pharmacodynamic components of shenkang injection, HSYA comes from safflower, which can inhibit platelet aggregation and release induced by platelet-activating factors, and can competitively inhibit the binding of platelet-activating factors and platelet receptors. HSYA is an effective component of safflower yellow pigment in promoting blood circulation and removing blood stasis [ 22 ]. Tanshinol, derived from Salvia miltiorrhiza, can improve the damage degree of blood vessels and enhance their growth ability, and can effectively play an anti-inflammatory role [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hydroxysafflor yellow A (HYSA), a natural compound from safflower, has a good effect of alleviating atherosclerosis, and clinical trials is needed (Xue et al, 2021). A meta-analysis with 31 groups containing a total of 2487 participants confirmed that HSYA can effectively treat diabetic kidney disease (DKD), which may provide therapies for DKD with new insights and promote its application in clinical practice (Fu et al, 2022). Besides, as unique organelles with a natural resilience to environmental stresses, safflower oleosomes may serve as a novel therapeutic agent in the field of dermatology, and human clinical research is required to determine their efficacy and safety (Patel et al, 2023).…”
Section: The Clinical Application Of Safflowermentioning
confidence: 99%
“…Fu et al. reported the improvement of HSYA in patients with DKD by improving biomarkers of oxidative stress and inflammatory response [ 119 ]. However, more RCTs are needed in the future to further demonstrate the effect and mechanism of HSYA in patients with DKD.…”
Section: Clinical Researchmentioning
confidence: 99%